2015
DOI: 10.1097/mnm.0000000000000368
|View full text |Cite
|
Sign up to set email alerts
|

Multiple and solitary skeletal muscle metastases on 18F-FDG PET/CT imaging

Abstract: Solitary SMM are less common than multiple on F-FDG PET/CT imaging. SMM are usually associated with other metastases and do not affect tumor staging. The cases of isolated SMM are very rare. Nevertheless, in patients with a diagnosis of malignant disease, a solitary, F-FDG avid intramuscular focus should be suspected to represent metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…According to Nocuń et al . 2015 [8], three patterns exists. The first pattern is multiple skeletal muscle metastasis generally accompanied by other metastases in lymph nodes and organs.…”
Section: Discussionmentioning
confidence: 99%
“…According to Nocuń et al . 2015 [8], three patterns exists. The first pattern is multiple skeletal muscle metastasis generally accompanied by other metastases in lymph nodes and organs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these advantages, the use of 18F-FDG PET/CT for the detection of STM of lung cancer has not been widely researched. In previous studies, the prevalence of STM varied from 0.86-13% [13,28]. In our review, we found that approximately 1.87% of patients with lung cancer had STM.…”
Section: Survival Timementioning
confidence: 57%
“…18 F-FDG PET/CT can show metabolic changes before morphological abnormalities occur, and is used to screen for extra-pulmonary metastases in patients with lung cancer [10]. It is a whole-body imaging technique, with high tumor-to-background FDG uptake ratio, which allows detection of hidden STM [13,28]. Despite these advantages, the use of 18F-FDG PET/CT for the detection of STM of lung cancer has not been widely researched.…”
Section: Survival Timementioning
confidence: 99%
“…Different mechanisms for metastasis to skeletal muscles are proposed. These include lymphatics, haematogenous, muscle trauma and surgical implantation 2 11. In the case reported by Tunio, they found two sites of muscular metastasis in gluteus maximus and rectus abdominis muscles in a 28-year-old man with known colon adenocarcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…Skeletal muscle metastasis is a very rare condition, accounting for less than 1% of metastasis, due to the improper environment of musculature for tumour growth 1 2. Despite its rare nature, it is reported in a large variety of primary malignancies including lung,3 lymphoma,4 renal cell carcinoma,5 gastrointestinal tract tumours,6 ovarian, thyroid, pancreatic and breast,7 with lung being the most common primary neoplasm 8.…”
Section: Introductionmentioning
confidence: 99%